Diversification of cephalic shield shape and antenna in phyllosoma I of slipper and spiny lobsters (Decapoda: Achelata) - José María Landeira; Diego Deville; Effrosyni Fatira; Zhixin Zhang; Sven Thatje; Qiang Lin; Santiago Hernández-León; Kaori Wakabayashi (Frontiers in Marine Science, 2023)
Slipper (Scyllaridae) and spiny (Palinuridae) lobsters show a complex life cycle with a planktonic larval phase, named phyllosoma. This unique larval form within Achelata (Decapoda) is characterized by a transparent dorsoventrally compressed body and a pair of antennae. This conspicuous morphology has been attributed to adaptive specialization of planktonic life. Early studies suggest that phyllosoma morphology has remained constant over the evolutionary history of Achelata, while recent evidence points out large morphological changes and that diversification of phyllosoma larvae is a consequence of radiation and specialization processes to exploit different habitats. Given the ecological and evolutive significance of phyllosoma, we used shape variation of the first phyllosoma stage (phyllosoma I) and a time-calibrated phylogeny of extant Achelata to study how diversification of phyllosoma I shape occurred along with the evolutionary history of Achelata. Our results show a conserved phyllosoma I with a pear-shaped cephalic shield and large antennae in spiny lobsters and older groups of slipper lobsters, yet highly specialized phyllosoma I with wide rounded cephalic shield and short antennae in younger groups of slipper lobsters. Analyses revealed two bursts of lineage diversification in mid and late history without a slowdown in recent times. Both bursts preceded large bursts of morphological disparity. These results joined with the allopatric distribution of species and convergence of phyllosoma I shapes between largely divergent groups suggest that diversification involves nonadaptive radiation processes. However, the correlation of a major direction of shape with the maximum distribution depth of adults and the occurrence of the second burst of diversification post-extinction of competitors within Achelata presuppose some ecological opportunities that might have promoted lineage and morphological diversification, fitting to the characteristic components of adaptive radiations. Therefore, we conclude that diversification of Achelata presents a main signature of nonadaptive radiation with some components of adaptive radiation.